Structure and Development of Laticifers in Embryos and Seedlings of Artocarpus heterophyllus Lam. - Tatang S. Suradinata (Journal of Mathematical and Fundamental Sciences, 1998)
Pada Artocarpus heterophyllus, pemula latisifer dibentuk dalam embrio pada awal perkembangan kotiledon. Pemula latisifier tersebut terdapat di tepi luar prokambium di daerah nodus kotiledon. Vesikula dalam berbagai ukuran merupakan komponen yang paling jelas dalam pemula latisifier tersebut. Selanjutnya pemula latisifier memanjang dan tumbuh secara intrusive sejajar dengan sumbu embrio kea rah radikula dan kotiledon. Dalam latisifier terjadi pembelahan inti tanpa diikuti sitokinesis, menghasilkan protoplas embrio kea rah radikula dan kotiledon. Dalam latisifer terjadi pembelahan inti tanpa diikutin sitokinesis, menghasilkan protoplas berinti banyak. Latisifer bercabang ke arah korteks dan empulur. Lateks dibentuk di dalam sitoplasma dan disimpan di dalam vakuola. Struktur latisifer adalah tak beruas dan bercabang. Tidak terjadi anastomosis di antara sel-sel latisifer yang letaknya berdekatan. Plasmodesmata jarang ditemukan pada dinding sel latisifer. Structure and Development of Laticifers in Embryos and Seedlings of Artocarpus heterophyllus Lam.In Artocarpus heterophyllus, laticifer initials are formed in the embryo at the beginning of the development of the cotyledons. The laticifer initials are located at the outer periphery of the procambium at the cotvledonary node. Vesicles of various sizes are the most conspicuous components in the laticifer initial. At subsequent growth, laticifer initials elongate parallel to the axis of the embryo and then grow intrusively towards the radicula and cotyledons. Nuclear division is not followed by cytokinesis and therefore a multinucleate protoplast is produced. The laticifers branch towards the cortex and the pith. Latex was built in the cytoplasm and stored in the vacuole. The structure of the laticifer are non-articulated and branched. No anastomosis occurs between adjacent laticifer cells. Plasmodesmata are rarely seen in the laticifer walls.